Immunohistochemical Analysis of 4-HNE, NGAL, and HO-1 Tissue Expression after Apocynin Treatment and HBO Preconditioning in Postischemic Acute Kidney Injury Induced in Spontaneously Hypertensive Rats - Sanjin Kovacevic; Milan Ivanov; Maja Zivotic; Predrag Brkic; Zoran Miloradovic; Rada Jeremic; Nevena Mihailovic-Stanojevic; Una Jovana Vajic; Danijela Karanovic; Djurdjica Jovovic; Jelena Nesovic Ostojic (MDPI AG, 2021)
Oxidative stress has been considered as a central aggravating factor in the development of postischemic acute kidney injury (AKI). The aim of this study was to perform the immunohistochemical analysis of 4-hydroxynonenal (4-HNE), neutrophil gelatinase-associated lipocalin (NGAL), and heme oxygenase-1 (HO-1) tissue expression after apocynin (APO) treatment and hyperbaric oxygenation (HBO) preconditioning, applied as single or combined protocol, in postischemic acute kidney injury induced in spontaneously hypertensive rats (SHR). Twenty-four hours before AKI induction, HBO preconditioning was carried out by exposing to pure oxygen (2.026 bar) twice a day, for 60 min in two consecutive days. Acute kidney injury was induced by removal of the right kidney while the left renal artery was occluded for 45 min by atraumatic clamp. Apocynin was applied in a dose of 40 mg/kg body weight, intravenously, 5 min before reperfusion. We showed increased 4-HNE renal expression in postischemic AKI compared to Sham-operated (SHAM) group. Apocynin treatment, with or without HBO preconditioning, improved creatinine and phosphate clearances, in postischemic AKI. This improvement in renal function was accompanied with decreased 4-HNE, while HO-1 kidney expression restored close to the control group level. NGAL renal expression was also decreased after apocynin treatment, and HBO preconditioning, with or without APO treatment. Considering our results, we can say that 4-HNE tissue expression can be used as a marker of oxidative stress in postischemic AKI. On the other hand, apocynin treatment and HBO preconditioning reduced oxidative damage, and this protective effect might be expected even in experimental hypertensive condition.